Perceptions of Al Jazeera arab satellite news channel's image among yemenis after its news coverage of the southern yemenis movement and the northern yemenis rebellion - Al-Harazi, Mustafa Al-Ezzi Naji (AUC Knowledge Fountain, 2010)
In the light of Al Jazeera recent heavy news coverage of the two Yemeni news events: the Southern Yemenis movement and the Northern Yemenis rebellion, this study aims to reveal perceptions of the channel's image among its Yemeni viewers. The study explores how popular the channel is in Yemen among other prominent Arabic-language news channels. It also reveals how its viewers perceive its credibility regarding its general news coverage and its news coverage of the two recent Yemeni events in specific. The study also focuses on the channel's non-viewers and why they do not follow news on Al Jazeera channel. The study is quantitative in nature where it uses a self-administered survey as a data collection tool. A total of 440 questionnaires were distributed to a non-probability purposive/quota sample targeting Sana'a city, the Capital of Yemen. Major Findings and Discussion: Among the primary study group (Al Jazeera viewers), the results reveal that Al Jazeera was rated the highest in popularity among other prominent Arabic-language news channels; however, the reasons behind its popularity were different from the reasons investigated by other studies. The two reasons with highest mean scores behind Al Jazeera popularity in Yemen are a) I follow news on Al Jazeera because it is a 24/7 news channel and b) I follow news on Al Jazeera because it carries extensive news coverage in Arabic. The two reasons with lowest mean scores are a) I follow news on Al Jazeera because it does not censor its news coverage and b) I follow news on Al Jazeera because its news sources are credible. Regarding the channel's credibility, its Yemeni viewers perceive Al Jazeera general news coverage somehow credible; however, they perceive it as a â not credible source' in its Yemen-related news coverage. A number of research hypotheses, which examine the relationship between education level, socioeconomic class and exposure against credibility, were all rejected. Such a result is backed up with Osgood's Congruity Theory that focuses on the attitudes held by individuals towards sources of information. It emphasizes how the strength of the relationship between the subject (Al Jazeera viewers) and object (their country: Yemen) determines the attitude held towards the media (Al Jazeera channel). Among the secondary study group (Al Jazeera non-viewers), the results show that Al Jazeera ranked fourth in popularity after Al Arabiya, BBC Arabic and Al Hurra. The reasons which most non-viewers chose to reflect why they do not follow news on Al Jazeera channel are a) it exaggerates its reporting on news events, b) I trust my social networks' (friends, family, co-workers, etc) opinions who think Al Jazeera news coverage is biased, c) I follow other news channels that my social networks (friends, family, co-workers..etc) trust to be reliable, and d) its news coverage of Yemen-related events is biased. Such a result is backed up by Newcomb's Symmetry Theory and the Two-Step Flow concept which both emphasize the importance that interpersonal communication can play in a society.